2019
DOI: 10.5530/ijper.53.3.80
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Stability Studies of Fast Disintegrating Tablets of Amlodipine Besylate

Abstract: Introduction: Among tablets, fast dissolving technology has gained considerable popularity due to their rapid onset of action. Amlodipine besylate (ADB) is a longacting calcium channel blocker that is used in the treatment of angina and hypertension which are life-threatening conditions and require immediate relief. Currently, no fast dissolving tablet dosage form of ADB is commercially available. Methods: A total of seven fast disintegrating tablets of Amlodipine besylate (ADB) have been prepared by direct co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Comparing these results with the results obtained in our study, it can be concluded that the excipients and primary packaging play a significant role in the photoprotection of amlodipine besylate. The impact of primary packaging (Alu/Alu blister) was observed on the stability of amlodipine besylate in rapidly disintegrating tablets for 6 months under real (30 °C, 65% of relative humidity) and stress (40 °C, 75% of relative humidity) conditions [19]. In both cases, the decrease in the content of amlodipine besylate was lower than 5%.…”
Section: Selectivitymentioning
confidence: 99%
“…Comparing these results with the results obtained in our study, it can be concluded that the excipients and primary packaging play a significant role in the photoprotection of amlodipine besylate. The impact of primary packaging (Alu/Alu blister) was observed on the stability of amlodipine besylate in rapidly disintegrating tablets for 6 months under real (30 °C, 65% of relative humidity) and stress (40 °C, 75% of relative humidity) conditions [19]. In both cases, the decrease in the content of amlodipine besylate was lower than 5%.…”
Section: Selectivitymentioning
confidence: 99%
“…Dropping height should be 6 inches on each rotation. The friability each batch was determined calculated using the following formula 15 :…”
Section: Evaluation Of Fast Disintegrating Tabletsmentioning
confidence: 99%
“…Telmisartan, olmesartan, and irbesartan are available on the market in combination with amlodipine and hydrochlorothiazide (Figure 1), manufactured by the same or different pharmaceutical industries [4]. Different analytical methods such as spectrophotometric [11][12][13][14][15][16][17][18], derivative spectrofluorimetric [19], HPLC [20][21][22][23][24][25][26][27], electrophoresis [28], and HPTLC [29] were reported for the concurrent determination of sartans, amlodipine, or hydrochlorothiazide from formulations and biological fluids. The literature has also reported a few analytical methods for the concurrent determination of ternary mixtures of sartans, amlodipine, and hydrochlorothiazide [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%